In defense of social and economic human rights: an intellectual history, 1940 to the present - Christiansen, Christian Olaf (Human rights in history, 2025)
"In this groundbreaking intellectual history of economic and social human rights, Christian Olaf Christiansen traces their justification from World War II until the present day. Featuring a series of fascinating thinkers, this is the first book to comprehensively map the key arguments made in defense of human rights"-- Provided by publisher